Exploring young people's understanding of culture: a study from Northern Ireland. Issue 1 (1st January 2020) - Durrer, Victoria; Kelly, Grace; McKnight, Martina; Schubotz, Dirk
ABSTRACT: This article highlights the need for greater understanding of the role that historical, socio-cultural and political context play in shaping perceptions of culture and cultural value. Findings draw on the annual attitudinal survey of 16-year-olds in Northern Ireland, Young Life and Times (2016), and four follow-up focus group discussions. Results complement existing cultural participation research, which relates forms of engagement with intersectional factors: age, location of residence, gender and income. Reflecting, to some degree, the specificities of the study's location in Northern Ireland, we also found that cultural participation and understandings of what counts as culture have strong connections to history, place, religion, tradition and family. Furthermore, while participants placed a high level of personal importance on the informal activities in which they engage daily, those activities associated with tradition and family were perceived as having higher cultural importance.